FENOMENA PEMBERITAAN INFORMASI KEAMANAN APLIKASI TIKTOK DI MEDIA ONLINE DALAM PEMAKAIAN APLIKASI TIKTOK - pramelani (Communications, 2021)
From year to year, social media users are increasing. This can also be seen from the emergence of social media applications that are growing and the number is more than one. However, along with these developments there are applications circulating which do not have official permits so they are considered illegal. One of them is TikTok cash. The name of this application has the same name as the TikTok social media application which is most popular at number one in the world. Meanwhile, Facebook is in second place. TikTok's fame has not been spared by the presence of information in online media that has emerged regarding the security of the application. The TikTok application is said to have a risky security hole where cyber criminals easily enter user accounts so that they can harm the account owner. To prevent this, the account owner is notified to update the latest TikTok application. Seeing this phenomenon, researchers are very interested in writing about the effect of the TikTok application's security information on online media on the attractiveness of social media users in using the TikTok application. The author uses social media users who are in Jakarta as respondents in this study. The method used in this research is a qualitative method. Data taken from observation, literature study and interviews. Then, this research can draw the following results: the effect of the security information of the TikTok application on online media makes social media users gain insight into the knowledge to use social media properly, comfortably and safely. In addition, respondents are not too concerned about security information in the online media because Check point research also advises TikTok application users to update the latest TikTok application and provide personal data. The attractiveness of social media users using the TikTok application is limited to connoisseurs because there are still things that are more interesting, namely YouTube and Instagram which are safer and attract content. Keywords: Information effect, Online media, attractiveness, social media